Rituximab for Autoimmune Encephalitis with Epilepsy. (23rd June 2020) - Kurukumbi, Mohankumar; Dave, Rahul H.; Castillo, Jose; Shah, Tulsi; Lau, Joanne
Abstract : Intractable epilepsy remains a significant medical challenge, resulting in recurrent and prolonged intensive care unit (ICU) admissions. Autoimmune encephalitis is emerging as a treatable cause of intractable epilepsy. It is characterized by antibodies against cerebral antigens, such as potassium channels such as leucine-rich, glioma inactivated 1 (LGI1) and contactin-associated protein 2 (CASPR2), calcium channels such as the voltage-gated calcium channel (VGCC), or neurotransmitter receptors such as the α -amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR), gamma aminobutyric acid receptor (GABAR), and N -methyl-D-aspartate receptor (NMDAR). Diagnosis requires a syndrome consistent with an antibody identified in serum or cerebrospinal fluid (CSF) using methods that minimize risk of false-positives. Although there is no officially approved therapy for these disorders, typical approaches involve chronic high-dose steroids, intravenous immunoglobulin (IVIG), or plasma exchange. Rituximab is effective for antibody-associated disorders such as lupus, myasthenia gravis, and neuromyelitis optica. Here, we present three patients who were admitted with recalcitrant status epilepticus and demonstrated serum antibodies against NMDAR, LGI1, or VGCC using a cell-based assay. All patients demonstrated complete, long-term epilepsy control and improvement in symptoms with rituximab.